Stress distribution among periodontally compromised abutments: A comparative study using three-dimensional finite element analysis - Rajkiran Chitumalla; Swapna Munaga; Amit Khare; Surendra Agarwal; Anjali Bhoyar; Swapnil Parlani (Wolters Kluwer Medknow Publications, 2012)
Aims: The aim of the study was to evaluate the stress distribution patterns in teeth and supporting structures of fixed prosthesis and design modifications in a fixed prosthesis with either normal or reduced bone support of an additional abutment. Study was also undertaken to disprove Ante's law. Materials and Methods: Main models and variations of main models (modification 1, 2, 3, 4, 5, 6, 7, 8) were subjected to 200 N at angulations of 90° and 15° on functional cusps. Results for each loading were obtained as stress distribution color images and numerical values were recorded. A three-dimensional finite element analysis study of variations of normal models was performed using two finite element softwares, namely PRO-Engineer wildfire version 1.0 manufacturer: Parametric technology corporation, Needham, MA 02494 U.S.A. Results: When periodontal compromised abutment teeth was splinted with an additional abutment an increase of stress was observed in periodontally compromised abutments so an additional abutment is not required. Eventhough the pericemental area of compromised abutments with an additional abutment (canine) was more than the combined pericemental area of pontics to be replaced, stress generated was more on abutments. This disproves Ante's law. Hence, it may be a reference, but should not be the ultimate criterion in determining the number of multiple abutments. Conclusions: When periodontal compromised abutment teeth was splinted with an additional abutment an increase of stress was observed in periodontally compromised abutments so an additional abutment is not required. Even though the pericemental area of compromised abutments with an additional abutment (canine) was more than combined pericemental area of pontics to be replaced, stress generated was more on abutments. This disproves Ante's law. Hence, it may be a reference, but should not be the ultimate criterion in determining the number of multiple abutments.